Synkope, epileptischer oder psychogener Anfall? Der Weg zur richtigen Diagnose - Baumgartner, Tobias; Surges, Rainer (DMW - Deutsche Medizinische Wochenschrift, 2019)
Transient loss of consciousness (TLOC) is a frequent cause of referral to an emergency room. In view of the impact on treatment and the patients’ daily life activities (e. g. profession, driving license), an accurate and timely diagnosis is of uttermost importance. This article provides key features and suggests a practical step-by-step approach of how to differentiate syncope, epileptic and psychogenic non-epileptic seizures as the commonest causes of nontraumatic TLOC.
Keywords: kurzzeitiger Bewusstseinsverlust; epileptischer Anfall; Synkope; psychogener nicht-epileptischer Anfall